2008
DOI: 10.1007/s00192-008-0670-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pregnancy on pelvic floor dysfunction and body image; a prospective study

Abstract: Impact of pregnancy on pelvic symptom-related quality of life and body image has not been previously documented. We hypothesize that pregnancy will have a negative impact on pelvic symptoms and body image. Pregnant subjects completed questionnaires in the first (S1) and third trimester (S2) and 6 months postpartum (S3) including: Body Exposure During Sexual Activities Questionnaire, Urogenital Distress Inventory, Incontinence Impact Questionnaire, and Fecal Incontinence Quality of Life Scale. Urinary symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 34 publications
3
18
0
9
Order By: Relevance
“…Mean Brink score was 9.1 ± SD, and fecal incontinence was reported by 14% of women (11). Our finding that sexual activity decreases as pregnancy progresses has been demonstrated by other trials (12, 13, 28-32). …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Mean Brink score was 9.1 ± SD, and fecal incontinence was reported by 14% of women (11). Our finding that sexual activity decreases as pregnancy progresses has been demonstrated by other trials (12, 13, 28-32). …”
Section: Discussionsupporting
confidence: 87%
“…Many women experience a decline in sexual activity and function while pregnant. (12, 13). While various studies have addressed pelvic floor changes during pregnancy, few have focused on primiparous women exclusively, addressed pelvic floor function comprehensively and gathered data across all three trimesters.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of this study are in agreement with the results obtained in previous studies focusing on the effect of cognitive behavioral therapy on other groups, including the effectiveness of cognitive behavioral therapy in negative body image (23,24,29), body image of women under mastectomy (25), and body image of Iranian girl students (26) in addition to studies dealing with the effectiveness of cognitive behavioral therapy in those who are suffering from body dysmorphic disorder (32,34,37), persons with binge eating disorder (33,35), and burnt women (36). No exclusive study has been carried out using Cash's cognitive behavioral therapy on primiparous women's body image, although there are much evidence on vulnerability of body image in this group of women (8)(9)(10)(11)(12)(13)(14) and psychiatric problems associated with as well (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there is a relationship between body dissatisfaction after delivery and psychiatric depression (9). Several studies have confirmed the mothers' body image disorder after delivery in comparison with pre-pregnancy period and even during pregnancy (8)(9)(10)(11)(12)(13)(14); therefore, treatment of body image disorders is an increasingly considerable issue (2,15).…”
Section: Introductionmentioning
confidence: 99%
“…Em relação aos sentimentos positivos, a maternidade é considerada muitas vezes o principal sentido na vida 19 . Apesar de nesta pesquisa a imagem corporal ser uma das facetas com melhor avaliação, pesquisas mostram que a imagem corporal é negativamente impactada devido às mudanças físicas em pouco tempo 20,21 . No domínio Meio Ambiente, a faceta com melhor avaliação foi o cuidado de saúde, o que reafirma a satisfação que essas gestantes estão sentindo em relação principalmente ao trabalho da equipe da ESF, ao qual elas se encontram vinculadas.…”
Section: Qualidade De Vida E Promoção Da Saúde: Em Foco As Gestantesunclassified